KARYA TARI MANYESO TERINSPIRASI DARI RITUAL MANDAGHAI DI DESA LUMINDAI KECAMATAN BARANGIN KOTA SAWAHLUNTO - Andriani, Auliya May; Erman, Syaiful; Ernawita, Ernawita (Institut Seni Indonesia Padangpanjang, 2023)
The Maarak tambun process aims to gather from the family and niniak mamak to find an agreement in the implementation of the batagak house. Maarak Tambun has two kinds of rituals, namely, Mandaghai (bloody), and mamujo (worshipping). The methods that were born in the concept of this manyeso dance work include observation, data processing, literature study, selection of dance supporters, exploration, movement arrangement, improvisation, and evaluation. The form in the manyeso dance has three parts, the first part describes the pain experienced by all family members and does not go away, the second part is a problem experienced by a person so that he becomes limping when carrying it. In this section, the property of the fabric is described as a problem that binds the dancer's body parts. The conflict in this work is the struggle for cloth with the intention that the problems that occur are like a tug of war that is being felt by someone. The third part of the problem can be solved if we draw closer to Allah.